Penanaman Jiwa Nasionalisme Melalui Sinema Konseling Sufistik - Cintami Farmawati (Madaniyah, 2019)
This research aims to determine the effect of sufistic counseling cinema in instilling the soul of nationalism. The research method used is true experiment with pre-posttest design with control group. The research subjects were 16 students, who were selected by purposive sampling. Sufistic counseling cinema consists of three stages: takhalli, tahalli and tajalli. Data collection using the scale of nationalism soul with validity coefficient from 0.658 to 0.932 and reliability coefficient of 0.922. Data analysis used U Mann-Whitney. The results showed a significant value of the nationalism spirit scale in the experimental group=0.035 (p<0.05), which means that there was a significant effect on nationalism soul in the experimental group between before and after being given treatment in the form of sufistic counseling cinema. Meanwhile, in the control group there was no significant effect between the pre-post test score in planting the spirit of nationalism with a score of 0.175> 0.05.